Donor-Site Morbidity Analysis of Thenar and Hypothenar Flap - Dong Chul Lee; Ho Hyung Lee; Sung Hoon Koh; Jin Soo Kim; Si Young Roh; Kyung Jin Lee (Archives of Plastic Surgery, 2024)
Background For the small glabrous skin defect, Thenar and Hypothenar skin are useful donors and they have been used as a free flap. Because of similar skin characteristics, both flaps have same indications. We will conduct comparative study for the donor morbidity of the Free thenar flap and Hypothenar free flap.